Policing Legitimacy Social Media, Scandal and Sexual Citizenship - Ellis, Justin R. (Crime and Justice in Digital Society, 2021)
This book critically analyses the impact of digital media technologies on police scandal. Using an in-depth analysis of a viral bystander video of police excessive force filmed at the 2013 Sydney Gay and Lesbian Mardi Gras Parade and uploaded to YouTube, the book addresses the ways social media video sousveillance can shape operational and institutional police responses to police misconduct. The volume features new research on the immediate and longer-term impacts of social media-generated police scandal on police legitimacy and accountability and responds to inherent questions of procedural justice. It interrogates the technological, political and legal frameworks that govern the relationships between the police and LGBTQI communities in Australia and beyond through the 'social media test' - the police narratives created and contested through social media, mainstream media, and police media. In doing so, it considers the role of sexual citizenship discourse as a political, economic and social organizing principle. A comprehensive and interdisciplinary understanding of 'digital' and 'queer' criminology, this is an essential read for those working at the intersection of criminology and the digital society, queer criminology, and critical criminology